Shear performance of reinforced ultra-high performance concrete rectangular section beams. (October 2020) - Wang, Qiang; Song, Hua-Lin; Lu, Chun-Ling; Jin, Ling-Zhi
Highlights: The shear behavior of 14 reinforced UHPC rectangular section beams was studied. Based on the particularity of UHPC material, failure modes of UHPC beams were summarized, the shear mechanism was revealed. The main components of shear capacity and their respective weights are summarized, and their influencing factors are analyzed. The calculation model based on plasticity theory was modified and the applicable conditions of the model were discussed. Abstract: Ultra-high performance concrete (UHPC) is an cement-based composite material with excellent durability and mechanical properties. Compared with normal concrete (NC), its composition is different and its strength is ultrahigh. As an alternative to NC, more and more attention has been paid to its performance especially for shear performance of working with steel bars. In this paper, the shear performance of 14 reinforced UHPC rectangular section beams with different shear span ratio, stirrup ratio, steel fiber volume ratio, reinforcement ratio and longitudinal reinforcement strength was studied. The failure mode and shear capacity calculation model based on plasticity theory of the beams were discussed. The results show that increasing the beams' shear span ratio in a certain range can obviously decrease the beams' shear capacity. Increasing the beams' stirrup ratio, reinforcement ratio and longitudinal reinforcement strength in a certain range can slightly increase the beams' shear capacity. When the steel fiber volume ratio is less than 1%, the shear capacity of the beams is low and the failure mode shows obvious brittleness. For beams without web reinforcement, when the shear span ratio is 1.5, the failure mode is diagonal compression failure and when the shear span ratio ranged from 1.75 to 3, it shows shear compression failure. There is a main obviously diagonal crack from the support to the loading point when the beams with stirrup ratio less than 0.45% fail. When the stirrup ratio is increased from 0.25% to 0.45%, the shear ductility is obviously improved. The calculation model based on plasticity theory can well estimate the shear capacity of beams with "shear compression failure" mode. The applicable conditions of the model should not be ignored.